Pattern Matching Filter and multielectrode mapping catheter – A new approach for complex premature ventricular contraction ablation - Sousa, Pedro A. (2021)
Purpose: Our goal was to assess usefulness of Pattern Matching Filter (PMF) software combined with the PentaRay catheter for complex premature ventricular contraction (PVC) ablation. Methods: A prospective observational study of consecutive patients referred for complex PVC ablation at our tertiary center from January to September 2018. Patients underwent ablation using a pre-specified mapping strategy with the PMF and the PentaRay catheter (PVCs with ≥97% correlation with the template morphology were collected). Procedural endpoints and acute and 12-months success rates were assessed and compared to a retrospective cohort of patients who also underwent a complex PVC ablation with standard activation mapping performed with a Thermocool SmartTouch catheter. Results: During the nine-month enrollment period, seven patients fulfilled our inclusion criteria, while there were four patients in the control group. Patients treated with the PMF and PentaRay had a fivefold number of points acquired (507±213 vs. 90±62) and a halved procedure time (67±42 vs.130±54 min), required a shorter radiofrequency ablation time (294±112 vs.706±613 sec) and had a higher overall success rate (100% vs.75%) when compared to the standard approach. No major complications occurred in either group. Conclusions: In this first study assessing the combined use of the PentaRay catheter and the PMF for complex PVCs ablation, we demonstrate how this approach can improve the level of detail, accuracy and reliability of the activation map, while reducing the number of radiofrequency applications and procedural time. Further studies are warranted to confirm whether this approach can lead to improved outcomes.